Application Of The Capital Asset Pricing Model (CAPM) Method In Determining Efficient Stock Group (Study On IDX30 And Business Index-27 In Indonesia Stock Exchange) - Anwar Anwar; Nurul Rahmah Dewi; Uhud Darmawan Natsir (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The purpose of this study is to classify efficient and inefficient stocks using the CAPM method so that investors can make the right investment decisions on the IDX30 and Bisnis-27 Index on the Indonesia Stock Exchange for the 2018-2022 period. The data used in this research is secondary data of 18 samples. The findings in this study, it can be seen that the greater the systematic risk (β), the smaller the expected rate of return E(Ri). This shows that there is a non-linear or non-linear relationship between (β) and E(Ri). Because the average beta value is less than 1 which indicates that stock prices tend to rise or fall lower than the market price index or Rm in general. The criteria for determining investment decisions are choosing efficient stocks. Efficient stocks are stocks that have levels individual returns that are greater than the expected rate of return or [Ri > E(Ri)], while eliminating inefficient stocks, namely stocks that have individual returns smaller than the expected rate of return or [Ri < E(Ri)]. The investment decisions made on efficient stocks are considering buying these shares and the decisions made on inefficient stocks are considering selling these shares.